Strength of Arm Muscles and Leg Muscles on Smash Ability in Club Volleyballgames Gareno District Luwu - Iis Saputri; Ahmad; Irsan Kahar (Universitas Negeri Semarang, 2024)
This study aims to determine(1) The relationship between arm muscle strength and smash ability at Club Gareno district Luwu (2) The relationship between muscle streng and smash ability at Club Gareno district Luwu (3) smash ability on Club Gareno.This type of research uses the correlation method. The population in this study was the Gareno Club athletes, totaling 12 people. The sampling technique in this research used saturated sampling. The Instrumen for arm muscle strength is the push-up test, neck muscle strength is the squad jump test, and smash ability uses the smash test. The data analysis techniqye uses multiple regression tests with the help of the SPSS 26 program. The results of the research show that (1) There is a significant relationship between arm muscle strength and samash ability in Gareno ditsrict Luwu club athletes. Luwu, with a calculated r value of 0,575. (2) There is a significant relationship between muscle strength and smash ability in Gareno district Club athletes. Luwu, with a calculated r value of 0,974 (3) There is a significant relationship between arm muscle strength and cooling muscle strength on smash ability at Club Gareno district Luwu, with an fcount value of 83,276